2010
DOI: 10.1299/jmmp.4.652
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Magneto-thermo-mechanical Behaviors of Terfenol-D

Abstract: Magnetostrictive materials have been widely used in sensors, actuators and transducers for decades. However, their applications are limited by the nonlinear response to both the prestress and the environment temperature. In that case, systematical study on magneto-thermo-mechanical behaviors of magnetostrictive materials is needed. In this paper, a new magneto-thermo-mechanical experimental apparatus is developed by adding circulating oil bath system to our magneto-mechanical device. Magnetization and magnetos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…For example, Moffett et al 7 measured magnetostrictive strain, piezomagnetic coefficient d 33 , permeability µ T 33 and compliance coefficient s H 33 of magnetostrictive material Terfenol-D rod under eight groups of different bias fields and pre-stresses, and found that when compressive pre-stresses were applied along axial direction, the increase of magnetization and magnetostrictive strain obviously slowed down in low and moderate magnetic and Gao et al 9,10 measured the variety of magnetostrictive strain, magnetization and Young's modulus of Terfenol-D rod with bias magnetic field under different axial pre-stresses and temperatures. The above results provided the basis for examining the pros and cons of various magnetostrictive constitutive models, and helped us to better understand the magneto-thermo-mechanical characterizations of Terfenol-D. For other magnetostrictive materials, like Metglas, Gillette et al 11 measured the curve of magnetostrictive coefficient with magnetic field, and Spano et al 12 measured the magnetization curves of Metglas under different stresses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Moffett et al 7 measured magnetostrictive strain, piezomagnetic coefficient d 33 , permeability µ T 33 and compliance coefficient s H 33 of magnetostrictive material Terfenol-D rod under eight groups of different bias fields and pre-stresses, and found that when compressive pre-stresses were applied along axial direction, the increase of magnetization and magnetostrictive strain obviously slowed down in low and moderate magnetic and Gao et al 9,10 measured the variety of magnetostrictive strain, magnetization and Young's modulus of Terfenol-D rod with bias magnetic field under different axial pre-stresses and temperatures. The above results provided the basis for examining the pros and cons of various magnetostrictive constitutive models, and helped us to better understand the magneto-thermo-mechanical characterizations of Terfenol-D. For other magnetostrictive materials, like Metglas, Gillette et al 11 measured the curve of magnetostrictive coefficient with magnetic field, and Spano et al 12 measured the magnetization curves of Metglas under different stresses.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of magnetostrictive materials, in particular, that of giant Terfenol-D magnetostrictive, has been observed in several experiments (Anjanappa and Bi, 1994;Clark, 1980;Clark and Crowder, 1985;Domenjoud et al, 2019;Gao et al, 2010;Liang and Zheng, 2007;Moffett et al, 1991).…”
Section: Introductionmentioning
confidence: 93%
“…[20][21][22][23] However, the nonlinear constitutive model of magnetostrictive phase is complex and not intuitive for building an equivalent circuit model, so it is replaced by the magnetostrictive constitutive model with variable coefficients in this paper. Without regard to the thermal expansion effect, the constitutive equations are expressed as:…”
Section: The Establishment Of Modelmentioning
confidence: 99%
“…Now, many researchers dedicate to improving the linearity of the CME effect. 19 However, the magnetization and magnetostriction of the ferromagnetic materials show the strong nonlinear thermo-magneto-mechanical coupling characteristic [20][21][22][23] under the influences of bias magnetic field, pre-stress and temperature, which lead to the CME effect and the electric field controlled magnetization effect possessing the strong nonlinear coupling effects essentially. Thus, to carry out a research about the nonlinear converse magnetoelectric coupling effect under the multi-physical field loadings is very urgent and necessary.…”
Section: Introductionmentioning
confidence: 99%